2009
DOI: 10.1021/bi901220u
|View full text |Cite
|
Sign up to set email alerts
|

Universal Convergence of the Specific Volume Changes of Globular Proteins upon Unfolding

Abstract: Both pressure and temperature are important environmental variables, and to obtain a complete understanding of the mechanisms of protein folding, it is necessary to determine how protein stability is dependent on these fundamental thermodynamic parameters. Although the temperature dependence of protein stability has been widely explored, the dependence of protein stability on pressure is not as well studied. In this paper, we report the results of the direct thermodynamic determination of the change in specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 33 publications
7
35
0
Order By: Relevance
“…Second, in this and in previous studies (20,21) we find that pressure unfolding profiles shift to higher or lower pressures with changes in solution composition, but the volume changes remain constant, regardless of the pressure range over which the unfolding occurs. Moreover, measurements with PPC (22,23), which involve pressure changes of only 5 bar, reveal volume changes upon unfolding consistent with those measured using spectroscopic approaches.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Second, in this and in previous studies (20,21) we find that pressure unfolding profiles shift to higher or lower pressures with changes in solution composition, but the volume changes remain constant, regardless of the pressure range over which the unfolding occurs. Moreover, measurements with PPC (22,23), which involve pressure changes of only 5 bar, reveal volume changes upon unfolding consistent with those measured using spectroscopic approaches.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, the value of the volume change of unfolding is a strong function of temperature, both in magnitude and even in sign (25). Positive values of ΔV u have been measured at high temperature, resulting from a large difference in the coefficient of thermal expansion of the folded and unfolded states (23,26,27). Improved understanding of these effects will be required before successful structure-based predictions of pressure effects on proteins are possible.…”
Section: Discussionmentioning
confidence: 99%
“…Schweiker et al [37] performed a concise PPC study on volume changes of various small globular proteins (cytochrome c, lysozyme, ribonuclease A, ubiquitin, and eglin C) and two cavity mutants of eglin c, where an additional cavity in the core of the wild type of the protein was introduced by substitution of the larger valine amino acid residue to alanine. Using linear extrapolation of relative volume changes, DV/V, measured as a function of temperature, the authors showed that DV/V of proteins sharing the same intrinsic packing density converge to a common value at high temperatures, T ⁄ % 140°C, while others with more expanded structures -the two cavity-containing eglin c variants and cytochrome c -display significantly higher values of DV/V.…”
Section: Temperature Dependence Of the Volume Change Of Unfoldingmentioning
confidence: 99%
“…Despite the laborious nature of pressure techniques, numerous studies were devoted to determine the thermodynamic properties of pressure-induced protein unfolding [1][2][3][4][5][6][7][8][9][10][11][12][13]. Relatively high pressures are required to determine the volumetric properties of proteins, and that is probably the most serious obstacle for the pressure to become a standard descriptor of the thermodynamic state of a protein.…”
Section: Introductionmentioning
confidence: 99%